2020
DOI: 10.5539/elt.v13n8p46
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Assessment of the Common Writing Errors among Saudi Foundation Year Students: A Comparative Study

Abstract: This research explored the most common writing errors of Science and Arts students of the Foundation year program at a Saudi University that hinder them from achieving their course goals, learning outcomes and becoming efficient writers. The importance of this research stems from the fact that, it is a comparative study that shows the differences in writing errors between Science and Arts students and relates writing difficulties to students’ background education, family support, level of the languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Many studies have discussed the reasons behind the difficulties faced by Saudi students when writing in English (Alghammas & Alhuwaydi, 2020;Alshammari, 2020;Khadawardi, 2022). Other studies have examined the extensive number of challenges that Saudi students specifically confront when attempting to improve their English writing ability and have also detailed methods to overcome those difficulties (Ahmed, 2019;Alkodimi & Al-Ahdal, 2021;Almalki, 2020;Altamimi & Ab Rashid, 2019;Khadawardi, 2022;Khatter, 2019;Shousha et al, 2020). For instance, Alzahrani et al (2020) utilized a questionnaire to investigate the writing skills of 12th-grade Saudi learners and identify whether their writing ability needed improving.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Many studies have discussed the reasons behind the difficulties faced by Saudi students when writing in English (Alghammas & Alhuwaydi, 2020;Alshammari, 2020;Khadawardi, 2022). Other studies have examined the extensive number of challenges that Saudi students specifically confront when attempting to improve their English writing ability and have also detailed methods to overcome those difficulties (Ahmed, 2019;Alkodimi & Al-Ahdal, 2021;Almalki, 2020;Altamimi & Ab Rashid, 2019;Khadawardi, 2022;Khatter, 2019;Shousha et al, 2020). For instance, Alzahrani et al (2020) utilized a questionnaire to investigate the writing skills of 12th-grade Saudi learners and identify whether their writing ability needed improving.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Fifteen purposively selected respondents wrote an essay titled 'Appropriate word order in English matters' to understand the underlying reasons, opinions, and motivations (Shousha, Farrag & Althaqafi, 2020). As the approach was more cross-sectional than longitudinal, the essay was written within 25 minutes after which the researcher collected the scripts.…”
Section: 2data Collection Proceduresmentioning
confidence: 99%
“…The usage of different methods in many studies on spelling analysis of bilinguals is observed through the relevant literature. In some studies, a structured approach is adopted by addressing the elements such as grammar, spelling, and punctuation (Ahmad et al, 2015;Altiparmak & Demir, 2020;Ardila et al, 2017;Polad, 2018;Shousha et al, 2020), while a broader scope was created by including the (Cetinkaya, 2015;Yilmaz & Demir, 2020), cognitive and communicative elements in others. The errors were analyzed by categorizing them separately in terms of the related mother tongue and target language in some studies (Kaweera, 2013;Kosasih, 2019;Sijonu, 2018).…”
Section: Detection Of Writing Errorsmentioning
confidence: 99%